98.5k views
2 votes
The solution of a certain differential equation is of the form y(t)=aexp(7t)+bexp(11t), where a and b are constants. The solution has initial conditions y(0)=1 and y′(0)=4. Find the solution by using the initial conditions to get linear equations for a and b.

2 Answers

6 votes

Answer:

y(t) = a exp(3t) + b exp(4t) conditions, y(0) = 3 y'(0) = 3 y(0) = a exp(3 x 0) + b exp(4 x 0) = a exp(0) + b exp(0) = (a x 1) + (b x 1) = a + b y'(0) = 0 so the linear equation is, a + b = 3

Explanation:

User Asher Dunn
by
6.3k points
3 votes

Answer:

Explanation:

Given that the solution of a certain differential equation is of the form


y(t) = ae^(7t) +be^(11t)

Use the initial conditions

i) y(0) =1


1=a(1)+b(1)\\a+b=1 ... I

ii) y'(0) = 4

Find derivative of y first and then substitute


y'(t) = 7ae^(7t) +11be^(11t)\\y'(0) =7a+11b \\7a+11b =4 ...II

Now using I and II we solve for a and b

Substitute b = 1-a in II


7a+11(1-a) = 4\\-4a+11 =4\\-4a =-7\\a = 1.75 \\b = -0.75

Hence solution is


y(t) = 1.75e^(7t) -0.75e^(11t)